2017
DOI: 10.1177/0956797617722621
|View full text |Cite|
|
Sign up to set email alerts
|

The Wisdom in Virtue: Pursuit of Virtue Predicts Wise Reasoning About Personal Conflicts

Abstract: Most people can reason relatively wisely about others' social conflicts, but often struggle to do so about their own (i.e., Solomon's Paradox; Grossmann & Kross, 2014). We suggest that true wisdom should involve the ability to reason wisely about others' and one's own social conflicts.The present studies investigate the pursuit of virtue as a construct that predicts this broader capacity for wisdom. Results across two studies support prior Solomon's Paradox findings: participants (N = 623) expressed greater wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 26 publications
4
45
1
1
Order By: Relevance
“…We suspect the pursuit of these intrinsic values would also characterize wise people, who would be aware of what matters most, and be less focused on self‐image, fame, or materialism. Consistent with this, evidence from Huynh, Oakes, Shah, and McGregor () connects the pursuit of virtues such as giving to the community (an intrinsic aspiration) with indicators of wisdom.…”
Section: Sdt and Research On Wisdommentioning
confidence: 81%
“…We suspect the pursuit of these intrinsic values would also characterize wise people, who would be aware of what matters most, and be less focused on self‐image, fame, or materialism. Consistent with this, evidence from Huynh, Oakes, Shah, and McGregor () connects the pursuit of virtues such as giving to the community (an intrinsic aspiration) with indicators of wisdom.…”
Section: Sdt and Research On Wisdommentioning
confidence: 81%
“…This let us identify from which provinces they originated. To assess their attentiveness to the study while participating, we included two questions (Huynh et al, 2017). One question was the statement "I conscientiously attempted to follow instructions to the best of my ability, " which was rated on a Likert-type scale from 1 "none of the time" to 5 "all of the time."…”
Section: Participantsmentioning
confidence: 99%
“…Some initial evidence has shown that wise reasoning may serve such a purpose. As compared to intelligence, wisdom also appears to be uniquely associated with prosocial and eudaimonic tendencies (e.g., cooperative intentions and behavior, growth orientation; [49,[101][102][103]), a willingness to forgive friends and family members one has a dispute with [57], as well as more prosocial behavior in economic transactions [104]. Moreover, and particularly pertinent to intergroup issues, wisdom is associated with reduced political bias [105], reduced intergroup attitude polarization across several heightened intergroup conflicts [106] (unpublished manuscript), and the willingness to consider diverse viewpoints during political elections in the US [107], with such aspects of wise reasoning as an appreciation of diverse viewpoints facilitating accuracy in the forecasting of geopolitical events [108].…”
Section: Civic Discoursementioning
confidence: 99%